Pengaruh Suhu dan Jumlah Siung Terhadap Kualitas Keripik Buah Jeruk Medan (Citrus Sinensis L.) Menggunakan Penggorengan Vakum (Vacuum Frying) - Putri, Sindie Ariza; Asmara, Sandi; Kuncoro, Sapto; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2025)
Medan orange (Citrus sinensis L.) is one of the sweet orange varieties that is very popular in Indonesia, Medan orange has limitations in terms of storage period. Fresh orange generally has a relatively short shelf life, so the risk of damage or quality degradation is quite high during distribution and storage. Therefore, it is necessary to develop innovations in orange processing to increase added value and extend its shelf life. Processing fruit chips using the vacuum frying method is an innovative technique that can maintain the sensory and nutritional quality of the final product. This study aims to determine the effect of frying temperature and the number of cloves on the quality of Medan orange (Citrus sinensis L.) fruit chips. The parameters observed include yield, water content, frying time, aroma, taste, crispiness, color, and panelist preference level. The temperature variations used were 60℃, 70°C, and 80°C, while the number of cloves used was 1 clove, 2 cloves, and 3 cloves. The results showed that there was an interaction between the effect of temperature and the number of cloves. Increasing the frying temperature significantly affected the frying time, where higher temperatures produced chips with faster frying times. However, high temperatures also caused darker color changes. Meanwhile, a larger number of cloves in one frying session tended to slow down the water evaporation process, thus affecting the texture and final color of the product. Keywords: Medan Orange, vacuum frying, temperature, number of cloves.